The Role of Teachers in Developing the Character of Elementary School Students through Social Studies Learning (IPS) - La Ode Fajrul Islam Sabti; Jufri Agus; Jufri (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This research aims to analyze the multidimensional role of teachers in developing the character of elementary school students through Social Studies learning (IPS). The study was conducted using a literature review method on scholarly articles from Google Scholar for the period 2019–2025. The results indicate that teachers play a central role as agents of character transformation, functioning across five main dimensions: (1) as a contextual idol who models positive values in daily interactions; (2) as a value integrator who creatively internalizes moral, social, and citizenship values into IPS materials through systematic lesson planning (RPP), innovative methods (project-based learning, simulations), and character-based media such as digital comics; (3) as a character habituation facilitator through structured routines (such as 3S, religious activities, and flag ceremonies) that create a consistent environment for value internalization; (4) as a facilitator of social skills and care through collaborative learning and real social projects; and (5) as a responsible digital literacy guide in the technological era. However, the effectiveness of this role faces challenges such as an excessive focus on cognitive aspects, limited competency in character-based pedagogy, and external environmental influences. Therefore, systemic support is needed in the form of continuous teacher competency improvement, value-oriented flexible curricula, and strong synergy between schools, families, and communities. In conclusion, IPS learning facilitated by teachers with multidimensional roles and supported by a collaborative ecosystem serves as a strategic vehicle for shaping a future generation that is not only academically intelligent but also strong in character, integrity, and social care.